The Philosophy of Space-Time: Whence Cometh Matter and Motion? - Malek, Abdul (JOURNAL OF ADVANCES IN PHYSICS, 2016)
From the macrocosm to the microcosm, natural science has so far confirmed the most fundamental assertion of materialist dialectics that there can be no matter without motion and no motion without matter. This view of the objective reality is in sharp conflict with the one proposed by Albert Einstein in his theory of General Relativity (GR). According to Einstein, Since the theory of general relativity (GR) implies the representation of physical reality by a continuous field, the concept of particles and material points cannot play a fundamental part and neither can the concept of motion. The particle can only appear as a limited region in space in which the field strength or energy density is particularly high(1). This article offers a dialectical perspective of the internal dynamics of Space-Time-Matter-Motion of the infinite universe, mediated by the virtual particles of the quantum vacuum. It is at the same time a refutation of the finite, non-material and abstract four dimensional spacetime geometric manifold as the ontological basis of objective reality, proposed by Minkowski and Einstein.